Chasing Zero (An Agent Zero Spy Thriller-Book #9) - Jack, Mars (Lukeman Literary, 2020)
"You will not sleep until you are finished with AGENT ZERO. A superb job creating a set of characters who are fully developed and very much enjoyable. The description of the action scenes transport us into a reality that is almost like sitting in a movie theater with surround sound and 3D (it would make an incredible Hollywood movie). I can hardly wait for the sequel." --Roberto Mattos, Books and Movie Reviews CHASING ZERO is book #9 in the #1 bestselling AGENT ZERO series, which begins with AGENT ZERO (Book #1), a free download with nearly 300 five-star reviews. The Palestinians decide they want to make peace with Israel-and they want the U.S. President to broker the historic treaty on their territory. Agent Zero advises the President against the dangerous trip, but he insists on going. After a series of dramatic and shocking twists, the most dangerous 48 hours of Zero's life ensue, forcing him into an impossible mission: save the President at all costs. CHASING ZERO (Book #9) is an un-putdownable espionage thriller that will keep you turning pages late into the night. "Thriller writing at its best." --Midwest Book Review (re Any Means Necessary) "One of the best thrillers I have read this year." --Books and Movie Reviews (re Any Means Necessary) Also available is Jack Mars' #1 bestselling LUKE STONE THRILLER series (7 books), which begins with Any Means Necessary (Book #1), a free download with over 800 five star reviews!
Keywords: Dobrodružství, napětí, thrillery